Goal priorities and time management practices of student athletes - Gobunquin, Julie Ann de Vera
The study aimed to provide a description of how student-athletes prioritize their goals and manage their time. Sixty-five students from different team sports of the University of the Philippines, Diliman participated in the survey. The survey instrument consisted of four-point Liker Scale to measure their perception of time, time management skills, a scaled rubric for time management practices, a ranking of goals and priorities, and a time log. Both sports- and academic related goals were considered important but sports- related goals were given slightly higher priority. The overall perception of student-athletes regarding their time management skills is good, with an overall mean of 2.75. An overall mean of 2.90 indicated that they are generally perceived time to be linear and non-replaceable. They perceived that time management is important in order to succeed in school and in sports (overall mean of 2.88). Most student-athletes (34%) scheduled tasks only when there is an important activity or deadline. despite this, nearly half of the respondents reported that they balance their time between sports and academic activities while a third perceived that they spend more time with their sports than their academics. Although they rarely follow their time schedule and let time wasters intrude in their time plan (52%) most of the time, they evaluate (34%) and simplify their work to save time (55%). The time log showed that student-athletes spent the most amount of time in their personal daily routines (i.e. sleeping, eating and grooming) followed by study time, leisure time and training. The goals priorities, perception of time management skills and time management practices show that student-athletes see the importance of both sports and academics but appear to show slightly more concern and focus on sports-related matters. With the numerous sports- and academic-related demands on their schedule, they may be more likely to cope with sports-related activities that have clear structure and rules than the academic-=related demands that have periodic and varied complexities. Student-athletes had a generally good perception of time and time management and showed efforts to manage their time. However, they were not consistent in carrying out effective time management practices.